A unilateral intratonsillar abscess in an adult treated by antibiotic therapy and needle aspiration - Ku Ismail, Ku Qayrunnisa; Rozhan, Atikah; Leman, Wan Ishlah (Springer Nature, 2024)
Intratonsillar abscess (ITA) is a rare clinical phenomenon in pediatric and adult populations. Even though it is rather uncommon, ITA should be included in the differential diagnosis of tonsillitis, peritonsillitis, and peritonsillar abscess. A computed tomography (CT) scan serves as a diagnostic tool for confirming the presence of an ITA. Needle aspiration of the tonsil not only further confirms the diagnosis but as part of the treatment of ITA in this case. Here, we report a case of a 34-year-old gentleman who presented with acute painful right neck swelling associated with odynophagia, voice changes, and reduced oral intake with examination revealed muffled voice, trismus, right cervical lymphadenopathy, bulging of the right peritonsillar region and deviation of the uvula to the left. Intravenous antibiotic therapy started and proceeded with aspiration then incision and drainage of the right peritonsillar region done as the initial provisional diagnosis was a right peritonsillar abscess. However, no pus drained. Thus, contrast-enhanced computed tomography (CECT) of the neck was done to assess the abscess collection and confirm the diagnosis. Therefore, the diagnosis was revised to the right ITA as the CECT neck showed a hypodense collection in the right palatine tonsil. In our case, the patient was treated by aspiration of the right tonsil to drain the pus with the continuation of antibiotics. Subsequently, the symptoms improved and resolved. In this case, the ITA can be treated with antibiotics and needle aspiration without surgical intervention.